The ten-thousand year fever rethinking human and wild primate malarias - Cormier, Loretta A. (New frontiers in historical ecology, 2011)
"Malaria is one of the oldest recorded diseases in human history, and its 10,000-year relationship to primates can teach us why it will be one of the most serious threats to humanity in the 21st century. In this pathbreaking book Loretta Cormier integrates a wide range of data from molecular biology, ethnoprimatology, epidemiology, ecology, anthropology, and other fields to reveal the intimate relationships between culture and environment that shape the trajectory of a parasite. She argues against the entrenched distinction between human and non-human malarias, using ethnoprimatology to develop a new understanding of cross-species exchange. She also shows how current human-environment interactions, including deforestation and development, create the potential for new forms of malaria to threaten human populations. This book is a model of interdisciplinary integration that will be essential reading in fields from anthropology and biology to public health"--